Concept design for a RFID enabled student workbook - Grout, Ian; Cesar Rodrigues Da Silva, Alexandre [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
In this paper, the concept for a radio frequency identification (RFID) enabled student workbook is discussed and a prototype system developed. The workbook is a question-answer notebook in traditional paper format in which hand written solutions to student assignments are written. An embedded RFID tag in the workbook is then used for the student to store his/her solution to the attempted assignment questions at home. On entry to the classroom and once the questions have been attempted, an RFID reader in the classroom will retrieve the answers from the workbook, automatically collate the results and instantly provide a summary of these results for the individual student and the class as a whole. If problems are highlighted, the teacher can then investigate issues with individual students and review the answers provided in the workbook. © 2014 IEEE.
Keywords: Assessment; Automation; RFID interface